Contribution of OqxAB Efflux Pump in Selection of Fluoroquinolone-Resistant Klebsiella pneumoniae - Orsolya Szabo; Bela Kocsis; Nikolett Szabo; Katalin Kristof; Dora Szabo (Canadian Journal of Infectious Diseases and Medical Microbiology)
The role of OqxAB efflux pump in Klebsiella pneumoniae was investigated in correlation with ciprofloxacin exposure. K. pneumoniae SE23 and K. pneumoniae SE191 were isolated from urinary tract infections and were analyzed in this study. Each carried oqxAB resistance determinant and exhibited ciprofloxacin MIC of 0.06 and 0.5 mg/L, respectively. Tested strains were initially exposed to their ciprofloxacin MIC values for 24 hours. Later on, the ciprofloxacin exposition has been increased to a daily 1, 2, 4, and to a final 8 mg/L. Total cellular RNA was extracted at 30, 60, 90, and 120 minutes of initial exposure and after every 24 hours. Quantitative reverse-transcriptase PCR was performed from each RNA sample. Mutation in gyrA and parC genes was analyzed in each strain and multilocus sequence typing (MLST) was performed. Ciprofloxacin exposure selected resistant strain from K. pneumoniae SE191; by contrast, K. pneumoniae SE23 was not adjustable to the increasing ciprofloxacin concentrations. During initial exposure, both oqxA and oqxB expression remained low (2−ΔCt = 1-2.03). However, increasing ciprofloxacin promoted oqxB expression as it reached fold increase of 15.8–22.8, while oqxA expression was maintained (2−ΔCt = 2-2.15). An amino acid substitution Ser83Tyr in gyrA was detected in K. pneumoniae SE191, but no additional mutations occurred as consequence to ciprofloxacin exposure. MLST identified K. pneumoniae SE191 as ST274, while K. pneumoniae SE23 belonged to the novel ST2567. Ciprofloxacin concentration-dependent upregulation of oqxAB efflux pump in K. pneumoniae is clonally related and contributes to selection for higher level of fluoroquinolone resistance.